2021
DOI: 10.3389/fnins.2021.748165
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Physiomarkers of Anxiety and Depression in Parkinson’s Disease

Abstract: Objective: Anxiety and depression are prominent non-motor symptoms of Parkinson’s disease (PD), but their pathophysiology remains unclear. We sought to understand their neurophysiological correlates from chronic invasive recordings of the prefrontal cortex (PFC).Methods: We studied four patients undergoing deep brain stimulation (DBS) for their motor signs, who had comorbid mild to moderate anxiety and/or depressive symptoms. In addition to their basal ganglia leads, we placed a permanent prefrontal subdural 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 50 publications
(66 reference statements)
2
14
0
Order By: Relevance
“…Nevertheless, PD patients with depression and anxiety should be monitored closely for ICB symptoms since these patients seem to be more vulnerable ( Marín-Lahoz et al, 2019 ). In this study, correlation analysis within the PDICB+ group also revealed higher depression score related to reduced gray matter volume in the medial frontal cortex, a region which has been associated with ICB and depression ( de Hemptinne et al, 2021 , Imperiale et al, 2018 , Schmaal et al, 2017 , Voon et al, 2011 ). The medial frontal cortex is known to be involved in cognitive control, reward, and affective processes ( Putnam and Chang, 2021 , Ridderinkhof et al, 2004 ).…”
Section: Discussionsupporting
confidence: 60%
“…Nevertheless, PD patients with depression and anxiety should be monitored closely for ICB symptoms since these patients seem to be more vulnerable ( Marín-Lahoz et al, 2019 ). In this study, correlation analysis within the PDICB+ group also revealed higher depression score related to reduced gray matter volume in the medial frontal cortex, a region which has been associated with ICB and depression ( de Hemptinne et al, 2021 , Imperiale et al, 2018 , Schmaal et al, 2017 , Voon et al, 2011 ). The medial frontal cortex is known to be involved in cognitive control, reward, and affective processes ( Putnam and Chang, 2021 , Ridderinkhof et al, 2004 ).…”
Section: Discussionsupporting
confidence: 60%
“…Sensing closed-loop devices implanted for psychiatric or nonpsychiatric indications may be leveraged to further our understanding of mood fluctuations, social interactions, and affective disorders in ambulatory settings. [55][56][57] Our review has a number of limitations. Using the RDoC framework, we limited our search to positive and negative valence domains given their relevance to psychiatric behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Two bipolar recording channels were also obtained from the two pairs of contacts (contact pairs 8–9 and 10–11) on both ECoG strips. The DBS electrode (Medtronic Model 3387) and 4-contact flexible ECoG paddle (Medtronic Model 5387A) in each hemisphere were connected to an implantable neural stimulator (INS), such that each DBS electrode was connected to an independent INS ( de Hemptinne et al, 2021 ). In total, there were three bipolar recording channels per hemisphere, one sensing VC/VS activity, and two sensing OFC activity.…”
Section: Methodsmentioning
confidence: 99%